A Novel Approach to Surgical Markings Based on a Topographic Map and a Projected Three-Dimensional Image. Issue 5 (May 2016) - Schreiber, Jillian E.; Stern, Carrie S.; Garfein, Evan S.; Weichman, Katie E.; Tepper, Oren M.
Abstract : Summary: Surgical markings play a crucial role in the planning of plastic surgery procedures.1–4 However, despite their importance, they are often imprecise. For instance, when assessing patients in need of autologous fat grafting, surgeons often base markings on estimations of where volume deficiency exists and how much volume will correct the deficiency. In this article, the authors describe a novel approach to lipostructure, guided by a computer-based roadmap. A digital three-dimensional topographic surgical map is created using three-dimensional photography and analytic software and then projected as an image onto the patient in the operating room. This unique concept can be applied to most soft-tissue procedures in plastic surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V. Abstract : Supplemental Digital Content is available in the text.